2012
DOI: 10.1515/1935-1682.3203
|View full text |Cite
|
Sign up to set email alerts
|

The Prostitute's Allure: The Return to Beauty in Commercial Sex Work

Abstract: We estimate the earnings premium for beauty in an occupation where returns to physical attractiveness are likely to be important: commercial sex work. Using data from sex workers in Ecuador and Mexico, we find that a one standard deviation increase in attractiveness yields 10-15 percent higher earnings. Including controls for personal characteristics (communication ability and desirability of personality) cuts the beauty premium by up to one-half. Beautiful sex workers earn higher wages, have more clients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Characteristics of women in sex work that objectively appeal to all clients, including various physical or personality features, are difficult to measure. The economic literature has typically simplified these features by attempting to capture the physical attractiveness of FSWs or clients (Arunachalam and Shah, 2012; Islam and Smyth, 2012). Outside of sex work, there is some evidence from labour economics that attractiveness is associated with better bargaining outcomes, more generous treatment and greater cooperation in negotiation (Mulford et al , 1998; Solnick and Schweitzer, 1999; Rosenblat, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of women in sex work that objectively appeal to all clients, including various physical or personality features, are difficult to measure. The economic literature has typically simplified these features by attempting to capture the physical attractiveness of FSWs or clients (Arunachalam and Shah, 2012; Islam and Smyth, 2012). Outside of sex work, there is some evidence from labour economics that attractiveness is associated with better bargaining outcomes, more generous treatment and greater cooperation in negotiation (Mulford et al , 1998; Solnick and Schweitzer, 1999; Rosenblat, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies have shown that attractiveness matters for labour market outcomes in the context of various developed countries such as the US and Canada (Hamermesh and Biddle, 1994;Mocan and Tekin, 2010), United Kingdom (Harper, 2000), Germany (Gehrsitz, 2014;Oreffice and Quintana-Domeque, 2016), Australia (Borland and Leigh, 2014). A few studies have looked at the relationship in developing countries including Bangladesh (Islam and Smyth, 2012), China (Hamermesh et al, 2002), Ecuador and Mexico (Arunachalam and Shah, 2012). 1 This paper studies labour market returns to physical attractiveness in a previously unexplored setting: transition countries.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been termed the "beauty premium." It appears to be pervasive: versions of the beauty premium have been found in labor markets (e.g., Hamermesh and Biddle, 1994;Biddle and Hamermesh, 1998), college classrooms (Hamermesh and Parker, 2005;Sen et al, 2010;Ponzo and Scoppa, 2012), credit markets (Ravina, 2012), sex markets (Arunachalam and Shah, 2012), professional sports (Berri et al, 2011), and elections (Hamermesh, 2006;Leigh and Susilo, 2009;Berggren et al, 2010).…”
Section: Introductionmentioning
confidence: 99%